Judging the plausibility of arguments in scientific texts: a student–scientist comparison. (2nd April 2016) - von der Mühlen, Sarah; Richter, Tobias; Schmid, Sebastian; Schmidt, Elisabeth Marie; Berthold, Kirsten
ABSTRACT: The ability to evaluate scientific claims and evidence is an important aspect of scientific literacy and requires various epistemic competences. Readers spontaneously validate presented information against their knowledge and beliefs but differ in their ability to strategically evaluate the soundness of informal arguments. The present research investigated how students of psychology, compared to scientists working in psychology, evaluate informal arguments. Using a think-aloud procedure, we identified the specific strategies students and scientists apply when judging the plausibility of arguments and classifying common argumentation fallacies. Results indicate that students, compared to scientists, have difficulties forming these judgements and base them on intuition and opinion rather than the internal consistency of arguments. Our findings are discussed using the mental model theory framework. Although introductory students validate scientific information against their knowledge and beliefs, their judgements are often erroneous, in part because their use of strategy is immature. Implications for systematic trainings of epistemic competences are discussed.